DIVERSIFIKASI OLAHAN DAN KEMASAN GULA KELAPA - Sayyida Sayyida; Alwiyah Alwiyah; Ika Fatmawati (LPPM Universitas Wiraraja Sumenep, Jalan Raya Sumenep Pamekasan KM. 5 Patean Sumenep 69451, Telp. (0328) 673399 Fax. (0328) 673088, 2018)
The technology of coconut sugar making in the area of research is still elementary. To increase the selling price of coconut sugar, needed product diversification, and packaging of processed coconut sugar. The target of a program is KWT Al Cholihah and KWT Al Fatah at District of Dungkek. One of processed coconut sugar offered in this program is the product of brown sugar. Packaging provided in this program is a plastic pouch packaging with the label image so that it can increase the shelf life and consumer appeal. Through the program science and technology to the Community on KWT Al Cholihah and KWT Al Fatah at District of Dungkek, the outcomes expected are as follows: (1) skilled members of KWT in the manufacture of brown sugar in attractive packaging, (2) Products is a product produced in brown sugar and coconut sugar in beautiful packaging and (3) increase in sales of coconut sugar and brown sugar. Based on the results of the implementation, the response of KWT members is apresiasif and positive. Positive response is seen from the desire of members to resume the manufacture of brown sugar for the domestic industry. After the members of the training, the participants are motivated to produce and begin to be marketed in the neighborhood. Results of print in packaging sugar production and brown sugar are now sold in some modern stores in Sumenep like Alfamart and outside of Sumenep.